2016
DOI: 10.1053/j.jrn.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Are Nutritional Composed Scoring Systems and Protein-Energy Wasting Score Associated With Mortality in Maintenance Hemodialysis Patients?

Abstract: Of the 3 investigated scoring systems, SGA and MIS predict mortality in a period of 15.5 ± 5.4 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In patients with ESRD, increased PEW is associated with poor prognosis. A nutritional composed scoring system or dietary inflammatory index shows a correlation between PEW and prognosis in patients with ESRD [ 15 , 16 ]. The pathophysiological mechanisms of PEW have been suggested to be complex including derangements in muscle, adipose tissue, and the gastrointestinal, hematopoietic, and immune systems, complications related to deficiencies of multiple micronutrients, and the maladaptive activation of the inflammatory cascade [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ESRD, increased PEW is associated with poor prognosis. A nutritional composed scoring system or dietary inflammatory index shows a correlation between PEW and prognosis in patients with ESRD [ 15 , 16 ]. The pathophysiological mechanisms of PEW have been suggested to be complex including derangements in muscle, adipose tissue, and the gastrointestinal, hematopoietic, and immune systems, complications related to deficiencies of multiple micronutrients, and the maladaptive activation of the inflammatory cascade [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PEW is important to predict outcomes [8]. The practice guidelines and criteria for evaluating the nutritional status in ESRD patients recommend the coordinated use of biochemical measures, body mass, muscle mass, dietary intake, and an integrative nutritional scoring [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the CANUSA study revealed that, in CAPD patients, a 1 unit reduction in the SGA score corresponds to a 25% increase in mortality (Canada-USA (CANUSA) Peritoneal Dialysis Study Group, 1996). A recent research also supported the CANUSA study (Vogt & Caramori, 2016). To assess the nutritional state of adult dialysis patients, the NKF kidney disease/dialysis outcomes and quality initiative (K/DOQI) recommends the use of SGA (Ikizler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%